2018
DOI: 10.1007/s00431-018-3220-0
|View full text |Cite
|
Sign up to set email alerts
|

Day case paediatric tonsillectomy: a quality improvement project

Abstract: Tonsillectomy is one of the commonest ENT paediatric procedures. Recovery is best achieved at home, and cost-effectiveness of the day case pathway is significant in tonsillectomy. This project scrutinised the local practice regarding the effectiveness of day case pathway in paediatric tonsillectomy in a large regional teaching hospital. The project aimed to improve the rates of day case tonsillectomy discharges, to increase compliance of postoperative care with guidelines, and to assess long-term sustainabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Our study is one of the largest to investigate outcomes after paediatric tonsillectomy in the UK [12]. Several single‐site UK‐based studies found no differences in outcomes for children who were discharged the same day as undergoing tonsillectomy compared with those who stayed overnight [13–15]. However, day‐case tonsillectomy is not suitable for all children and clear criteria for patient selection are needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study is one of the largest to investigate outcomes after paediatric tonsillectomy in the UK [12]. Several single‐site UK‐based studies found no differences in outcomes for children who were discharged the same day as undergoing tonsillectomy compared with those who stayed overnight [13–15]. However, day‐case tonsillectomy is not suitable for all children and clear criteria for patient selection are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, a 3-year audit of practice concluded that day-case tonsillectomies can be successful in selected children, but noted that a dedicated day-case team, good anaesthetic technique, adequate postoperative analgesia and on-site paediatric inpatient facilities are essential to optimise outcomes [14]. Finally, a quality improvement programme reported an increase in tonsillectomy day-case rates and decreased costs without an increase in postoperative complications at an English-teaching hospital [15].…”
Section: Discussionmentioning
confidence: 99%